2021
DOI: 10.1242/dev.199644
|View full text |Cite
|
Sign up to set email alerts
|

FAM71F1 binds to RAB2A and RAB2B and is essential for acrosome formation and male fertility in mice

Abstract: The acrosome is a cap-shaped, Golgi-derived membranous organelle that is located over the anterior of the sperm nucleus and highly conserved throughout evolution. Although morphological changes during acrosome biogenesis in spermatogenesis have been well described, the molecular mechanism underlying this process is still largely unknown. Family with sequence similarity 71, member F1 and F2 (FAM71F1 and FAM71F2) are testis-enriched proteins that contain a RAB2B-binding domain, a small GTPase involved in vesicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…The number of pups was counted on the day of birth. For the in vitro fertility assay, in vitro fertilization (IVF) analysis was performed as previously described ( Morohoshi et al., 2021 ) with some minor changes. For ZP-free oocytes, sperm insemination was performed at a final density of 2 ​× ​10 4 spermatozoa/mL.…”
Section: Methodsmentioning
confidence: 99%
“…The number of pups was counted on the day of birth. For the in vitro fertility assay, in vitro fertilization (IVF) analysis was performed as previously described ( Morohoshi et al., 2021 ) with some minor changes. For ZP-free oocytes, sperm insemination was performed at a final density of 2 ​× ​10 4 spermatozoa/mL.…”
Section: Methodsmentioning
confidence: 99%
“…Data in the human protein atlas ( www.proteinatlas.org ) shows expression in human bronchial epithelium but whether it is regulated by CFTR expression per se is unclear. FAM71F1 has mostly been studied in spermatogenesis as it controls acrosome assembly and male fertility [27] which is a phenotype in CFTR deficient patients and whether there is a direct link of CFTR and FAM71F1 in these tissues remains to be determined. C5orf46 is expressed in epithelial cells and has recently been reported to encode an antimicrobial protein with activity against gram negative bacteria [28] .…”
Section: Discussionmentioning
confidence: 99%
“…FAM71F1 and FAM71F2 are testis specific proteins containing a RAB2B‐binding domain, which is a small GTPase involved in vesicle transport and membrane trafficking. Fam71f1 and Fam71f2 are both essential for proper acrosome formation and normal male fertility (Morohoshi et al, 2021). Our previous research showed that FAM71D, a protein predominantly expressed in the testis, could interact with calmodulin and was involved in sperm motility in vitro (Ma et al, 2017).…”
Section: Introductionmentioning
confidence: 99%